(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The study of anatomy remains the cornerstone of medical education, bridging fundamental knowledge of the human body with clinical practice. Classical anatomy provides a standardized framework for understanding normal human structures, while variational anatomy highlights deviations that may occur in different populations or individuals. Both approaches are critical in clinical practice, surgical procedures, radiology, and medical diagnostics. This article analyzes the clinical significance of classical and variational anatomy through a review of literature, methodological approaches, clinical observations, and implications for modern healthcare.